Closing the loop on thromboprophylaxis post caesarean section. (18th April 2012) - Imcha, M; Edoo, AWI; Ismail, MR; Cotter, A; Burke, G; Fahy, U
Abstract : Background: Venous thromboembolism is one of the leading causes of Direct Maternal Death. Caesarean section is a significant risk factor. The Royal College of Obstetricians and Gynaecologists (RCOG) issued guidelines for thromboprophylaxis following caesarean section. Objective: To evaluate our compliance with RCOG guidelines on timing and dosage of thromboprophylaxis in women undergoing caesarean section, to introduce changes in practice based on observations of this audit, and to re-audit our practices to assess the effect of the changes. Method: The initial prospective audit in June 2011 involved 18 consecutive post-caesarean section women. Data was collected on various attributes- age, BMI, type of Caesarean section and timing and dosage of low molecular weight heparin (LMWH). This information was compared with RCOG guidelines, changes introduced and re-audit carried out after 4 months. Results: The initial study revealed that all women had treatment with LMWH but at least 33% (6/18) had incorrect dose and BMI was not recorded for 20%. Timing of first dose ranged from 6-16.5 hrs. The following changes were introduced: Clinicians advised to document booking BMI Obstetricians encouraged to prescribe appropriate weight/time-related LMWH dose LMWH dose and timing tables placed in theaters and wards. Following introduction of these changes re-audit in October 2011 showed 95% had BMI recorded, 83 % had appropriate LMWH dose and first dose timing ranged from 4-12 hrs. Conclusions: Our audit shows that quality intervention and introduction of new clinical practices resulted in significant improvement in adherence with the RCOG guidelines, but further improvement could be achieved.